Nephrotoxicity induced by vascular endothelial growth factor inhibitors - Shirinsadat Badri (Society of Diabetic Nephropathy Prevention, 2022)
Vascular endothelial growth factor (VEGF) is a special mitogen for vascular endothelial cells, an essential endogenous angiogenic cytokine, and the principal controller of vascular growth that plays a fundamental role in therapeutic angiogenesis pathways. VEGF-targeted therapy is categorized into the group of angiogenesis inhibitors that inhibit the expression or the activity of VEGF. It comprises counteracting VEGF antibodies, VEGF receptors, VEGF-trap, and tyrosine kinase inhibitor (TKIs) with selectivity for VEGF receptors. The kidney is both a target and a source of VEGF. VEGF may be a vital mediator to restore some types of renal diseases (e.g., non-diabetic renal diseases) and harmful in some other diseases (e.g., diabetes and diabetes complications). Due to their ability to prevent angiogenesis, VEGF inhibitors have been found as a powerful tool to treat angiogenesis-dependent diseases, including cancer and diabetic retinopathy. VEGF preserves the renal structure and function in normal physiologic conditions. Therefore, all treatments that inhibit the VEGF pathway may lead to renal disorders, especially renovascular diseases such as hypertension, proteinuria, nephrotic syndrome, decreased glomerular filtration rate (GFR), and thrombotic microangiopathy (TMA). In the present study, we reviewed some related reports and associated mechanisms, especially for hypertension and proteinuria.